Oral Health Policy and Improvement Strategies in Oklahoma - Dennison, Michelle; Seward, Julie (Frontiers in Oral Health, 2022)
Oklahoma an ethnically, financially and geographically diverse population has unique oral health care challenges. These challenges include poor overall oral health, inadequate oral health coverage, significant physical access to care barriers and a shortage of oral health care workers. Just as the oral health care barriers are diverse, so are the potential solutions. Potential solutions include efforts at all levels of government, innovations of health care delivery and recognition of the unique needs of Oklahoma American Indian population. Potential strategies address each of these opportunities and recognize both the short and long term needs of Oklahoma oral health.